Психологічні особливості комунікації за допомогою месенджерів - Ушаков, А. М. (ХНУРЕ, 2020)
In recent years, the Internet has occupied a significant place in people's everyday lives. With the development of modern technologies, the Internet has moved to mobile phones, which has made it possible to stay online almost all the time, and therefore social communications have acquired new features. With the development of the Internet, it has become possible to use all its achievements, including messengers. Every year, the popularity of messengers increases, they become an integral part of modern life, and the number of regular users, especially young people, is growing. At the same time, this new form of communication is becoming one of the topical areas of scientific research.
Keywords: філософія; психологічні особливості комунікації